Analisis Kriminologis Kekerasan Seksual Terhadap Perempuan Dan Anak Di Kota Kupang - Sofie Jashinta Nalle; Rudepel Petrus Leo; Rosalind Angel Fanggi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Sexual violence is an incident that cannot be separated from women and children. The rise in incidents of sexual violence against women and children in the city of Kupang is a fluctuating phenomenon. The Kupang City Police PPA Unit noted that, in 2021 there were 42 cases of violence against women and children, in 2022 it decreased to 39 cases, and increased in 202 to 42 cases. This research aims to determine the factors that cause sexual violence against women and children, and determine the obstacles to solving criminal acts of sexual violence against women and children in Kupang City, as well as efforts to overcome them. This research uses empirical juridical methods, with the type of data used being primary data based on the results of interviews and documentation, as well as secondary data used to complement primary data. The results of this research show that (1) The factors causing sexual violence behavior are sexual desire, lack of sex education, social and environmental factors, and misuse of technology. (2) Obstacles experienced in resolving cases of sexual violence include insufficient evidence, individual factors, and the perpetrator running away. (3) The countermeasures that have been carried out are in the form of preemptive, preventive and repressive measures.